A nutrient sentinel stands guard outside the cell - Vigetti, Davide (J Biol Chem, 2018)
Nutrient sensing is a critical cell function that regulates survival and growth by adjusting metabolism. During nutrient shortage, autophagy enables the recycling of major cellular components to prevent cell death. Understanding the mechanisms that trigger and control autophagy is of fundamental importance, as this degradative pathway plays a pivotal role in many diseases. Gubbiotti et al. report the identification of a new player, the proteoglycan decorin, which functions as a nutrient sensor in the extracellular matrix and controls autophagy in the heart.